Opportunities and barriers for photovoltaics on multi-unit residential buildings: Reviewing the Australian experience. (April 2019) - Roberts, M.B.; Bruce, A.; MacGill, I.
Abstract: This paper reviews opportunities for, and barriers to, increasing photovoltaic (PV) deployment on apartment buildings, with a particular focus on the Australian experience. As rapid urbanisation drives increasing housing density, PV penetration in multi-occupancy housing has been limited by comparison with stand-alone housing in many jurisdictions, including in Australia despite its world-leading residential PV penetration. Given the growing commercial attractiveness of residential PV, this also raises equity concerns for apartment households. PV can potentially be installed to supply electricity to common property, to serve individual apartments, or as a resource shared between multiple apartments through embedded networks, local energy trading or 'behind the meter' deployment models. Our study undertook a review of the academic literature in this space and of specific Australian regulatory arrangements, as well as conducting a series of semi-structured interviews with a range of relevant stakeholders. Barriers identified include the huge variety amongst existing apartment building stock, demographic factors and knowledge issues. However, the Australian regulatory context - including governance of apartment buildings, regulation of the energy market, and electricity tariff policies - also impacts on the options available to apartment residents. New business models for deploying PV on apartments are emerging, including initiatives from retailers, developers and community energy organisations. While some issues are specific to the Australian context, or to buildings governed under strata-type arrangements, broader lessons can be taken from the Australian experience, including to inform the design of the regulatory framework required to facilitate widespread PV deployment across all residential housing types. Highlights: Photovoltaic deployment on apartment buildings faces multiple barriers. A range of technical and organisational models is emerging. Changes to the regulatory framework could support greater deployment.